2016
DOI: 10.13189/bb.2016.040501
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization and Screening for Anticancer and Antimicrobial Properties of the Crude Extract from Genus Neosartorya

Abstract: The genus Neosartorya, the sexual states of Aspergillus, belongs to the Eurotiales which have been reported for compounds with bioactivities such as antimicrobial, antimalarial and cytotoxicity. The objective of this research was to isolate, identify and screening for anticancer and antimicrobial properties of the ethyl acetate crude extract from Neosartorya. Neosartorya sp. was isolated from soil in Chiang Mai province, Thailand by the soil plate technique. The samples were identified base on morphology and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Sunil et al (2014) reported that Aspergillus oryzae produces a high level of L-Glutaminas and potential anti-oncogenic activity against the MCF-7 cell line of human breast cancer [22]. Supattra et al (2016) isolated Neosartorya hiratsukae and Neosartorya pseudofischeri from soil samples. They screened against several cancer cell lines, including HepG2, MCF-7, L929, HeLa, HT-29, L929, KB, Vero and P388 [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sunil et al (2014) reported that Aspergillus oryzae produces a high level of L-Glutaminas and potential anti-oncogenic activity against the MCF-7 cell line of human breast cancer [22]. Supattra et al (2016) isolated Neosartorya hiratsukae and Neosartorya pseudofischeri from soil samples. They screened against several cancer cell lines, including HepG2, MCF-7, L929, HeLa, HT-29, L929, KB, Vero and P388 [23].…”
Section: Introductionmentioning
confidence: 99%
“…Supattra et al (2016) isolated Neosartorya hiratsukae and Neosartorya pseudofischeri from soil samples. They screened against several cancer cell lines, including HepG2, MCF-7, L929, HeLa, HT-29, L929, KB, Vero and P388 [23]. It was seen that the ethyl acetate extract of N. hiratsukae and N. pseudofischeri displayed the highest anticancer activity against the L929 cell line compared to the other cell lines.…”
Section: Introductionmentioning
confidence: 99%